Genetic Regulation of the yefM-yoeBSpn Toxin-Antitoxin Locus of Streptococcus pneumoniae - Chan, W.T. (American Society for Microbiology, 2011)
Type II (proteic) toxin-antitoxin systems (TAS) are ubiquitous among bacteria. In the chromosome of the pathogenic bacterium Streptococcus pneumoniae there are at least eight putative TAS, one of them being the yefM-yoeB(Spn) operon studied here. Through footprinting analyses, we showed that purified YefM(Spn) antitoxin and the YefM-YoeB(Spn) TA protein complex bind to a palindrome sequence encompassing the -35 region of the main promoter (P(yefM2)) of the operon. Thus, the locus appeared to be negatively autoregulated with respect to P(yefM2) as YefM(Spn) behaved as a weak repressor with YoeB(Spn) as a co-repressor. Interestingly, a BOX element, composed of a single copy each of boxA and boxC sub-elements was found upstream of promoter P(yefM2). BOX sequences are pneumococcal, perhaps mobile, genetic elements that have been associated with bacterial processes such as phase variation, virulence regulation and genetic competence. In the yefM-yoeB(Spn) locus, the boxAC element provided an additional weak promoter, P(yefM1), upstream of P(yefM2) which was not regulated by the TA proteins. In addition, transcriptional fusions with a lacZ reporter gene showed that P(yefM1) was constitutive albeit weaker than P(yefM2). Intriguingly, the coupling of the boxAC element to P(yefM1) and yefM(Spn) in cis (but not in trans) led to transcriptional activation indicating that the regulation of the yefM-yoeB(Spn) locus differ somewhat from other TA loci and may involve as-yet unidentified elements. Conservation of the boxAC sequences in all available sequenced genomes of S. pneumoniae which contained the yefM-yoeB(Spn) locus suggested that its presence may provide a selective advantage to the bacterium.